The hippo signaling pathway: implications for heart regeneration and disease - Del Re, Dominic P (Clin Transl Med, 2014)
Control of cell number and organ size is critical for appropriate development and tissue homeostasis. Studies in both Drosophila and mammals have established the Hippo signaling pathway as an important modulator of organ size and tumorigenesis. Upon activation, this kinase cascade modulates gene expression through the phosphorylation and inhibition of transcription co-activators that are involved in cell proliferation, differentiation, growth and apoptosis. Hippo signaling serves to limit organ size and suppress malignancies, and has been implicated in tissue regeneration following injury. These outcomes highlight the important role that Hippo signaling plays in regulating both physiologic and pathologic processes. In this review, an overview of the signaling pathway will be discussed as well as recent work that has investigated its role in cardiac development, regeneration and disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40169-014-0027-0) contains supplementary material, which is available to authorized users.